2015
DOI: 10.1111/tid.12443
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged outbreak of adenovirus A31 in allogeneic stem cell transplant recipients

Abstract: An outbreak of HAdV in HSCT recipients can be difficult to control. Although none of the patients had severe disease, the medical consequences were significant. It is possible that unidentified cases with mild symptoms may have caused continuous transmission at the unit. Regular testing of all patients several weeks beyond the last case identified may be an important measure to control transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…Although respiratory HAdVs are detectable year round (Fig. 1), the impressive HAdV disease potential is demonstrated in regional and institutional outbreaks of certain subtypes (192)(193)(194)(195)(196)(197).…”
Section: Other Carvs In Sot and Allogeneic Hctmentioning
confidence: 99%
“…Although respiratory HAdVs are detectable year round (Fig. 1), the impressive HAdV disease potential is demonstrated in regional and institutional outbreaks of certain subtypes (192)(193)(194)(195)(196)(197).…”
Section: Other Carvs In Sot and Allogeneic Hctmentioning
confidence: 99%
“…Although variable, most studies reported that HAdV infection including viremia usually occurred within the first 100‐180 days after transplantation . Endogenous reactivation of latent virus was regarded as the major mode of infection; however, de novo infection in nosocomial and community settings could also occur . HAdV‐attributable mortality is approximately 1%; however, in disseminated cases, the rate may increase up to 80%‐100% .…”
Section: Introductionmentioning
confidence: 99%
“…In general, relatively mild viral infections in healthy individuals can be prolonged or more severe in immunocompromised children. If undetected they may spread among transplanted patients which could potentially lead to a clinical manifestation (Schwartz et al, 2011;Swartling et al, 2015;van der Doef et al, 2016). Interestingly, the mere presence of certain viruses in the gut both before HSCT (van Montfrans et al, 2015) and before or within 1 week after HSCT (Legoff et al, 2017) can be predictive of/predispose for the development of intestinal GVHD.…”
Section: Discussionmentioning
confidence: 99%